1998
DOI: 10.1023/a:1005959218524
|View full text |Cite
|
Sign up to set email alerts
|

The mannose 6-phosphate/insulin-like growth factor 2 receptor (M6P/IGF2R), a putative breast tumor suppressor gene

Abstract: Loss of heterozygosity (LOH) at the mannose 6-phosphate/insulin-like growth factor 2 receptor gene locus (M6P/IGF2R) on 6q26-27 has recently been demonstrated in approximately 30% of both invasive and in situ breast cancers. LOH was coupled with somatic point mutations in the remaining allele in several instances, leading to the proposition that M6P/IGF2R is a tumor suppressor gene. Somatic mutations in M6P/IGF2R have also been described in hepatoma and gastrointestinal cancers with the replication error posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 62 publications
0
64
0
2
Order By: Relevance
“…The IGF-I receptor mediates most of the biologic actions of both IGF-I and IGF-II (Cohick and Clemmons 1993), including the mitogenic, metabolic, and cellsurvival properties of IGFs through tyrosine kinase signaling activity. The IGF-II/mannose 6-phosphate receptor appears to be a bifunctional receptor serving as both a lysosomal enzyme-targeting system and a suppressor of the action of IGF-II by increasing its degradation (Nissley and Lopaczynski 1991;Oates et al 1998). The levels of IGF-I receptors in leiomyomas have been reported to exceed those of the myometrium in three studies (Chandrasekhar et al 1992;Tommola et al 1989; Van der Ven et al 1997), whereas Chandrasekhar et al found no difference in the levels of the IGF-II receptors.…”
Section: Growth Factors Identified In Fibroidsmentioning
confidence: 99%
“…The IGF-I receptor mediates most of the biologic actions of both IGF-I and IGF-II (Cohick and Clemmons 1993), including the mitogenic, metabolic, and cellsurvival properties of IGFs through tyrosine kinase signaling activity. The IGF-II/mannose 6-phosphate receptor appears to be a bifunctional receptor serving as both a lysosomal enzyme-targeting system and a suppressor of the action of IGF-II by increasing its degradation (Nissley and Lopaczynski 1991;Oates et al 1998). The levels of IGF-I receptors in leiomyomas have been reported to exceed those of the myometrium in three studies (Chandrasekhar et al 1992;Tommola et al 1989; Van der Ven et al 1997), whereas Chandrasekhar et al found no difference in the levels of the IGF-II receptors.…”
Section: Growth Factors Identified In Fibroidsmentioning
confidence: 99%
“…In fact, a number of studies have shown that loss of CI-MPR function can induce cell proliferation in a variety of cancers. 15,16 Conversely, a protective role for the receptor has been suggested by two lines of evidence: cultured PC12 cells that are resistant to ␤-amyloid-mediated toxicity show an up-regulation of the CI-MPR 17 and overexpression or activation of the CI-MPR can block cell death induced by the mutant herpes simplex virus 1 or retinoic acid. 18,19 Nevertheless, very little is cur-rently known about the role of the CI-MPR in regulating neuronal viability after toxicity/injury or in any of the neurodegenerative disorders associated with dysfunction of the EL system.…”
mentioning
confidence: 99%
“…IGFs have been implicated in growth regulation of breast cancer cells (4) since they are mitogenic to such cells (5) and also because blockade of the IGF receptor can reduce growth of the cells in the absence of estrogen (6). Breast cancer cell lines possess IGFII (7), make several of the IGFBPs (8), and have functional IGF receptors (5), both type I (IGFIR) (9) and type II (IGFIIR) (10).…”
mentioning
confidence: 99%